Investigation of wustite (Fe1-xO) by femtosecond laser assisted atom probe tomography - Bachhav, Mukesh N.; Danoix, R.; Danoix, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Vurpillot, F. (Ultramicroscopy, 2011)
In this paper, we report results obtained from laser assisted three-dimensional (3-D) atom probe tomography (APT) on wustite (Fe1-xO). Oxides are generally insulating and hence hard to analyse in conventional electrical assisted APT. To overcome this problem, femtosecond laser pulses are used instead of voltage pulses. Here we discuss some aspects of pulsed laser field evaporation and optimization of parameters to achieve better chemical accuracy. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Atom probe tomography; Laser assisted field evaporation; Wustite